2017
DOI: 10.38036/jgpp.9.1_1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Electrode Plasma Actuator to Improve Performance of Flow Separation Control

Abstract: The advantage of a trielectrode (TED) plasma actuator in the flow separation control on the two-dimensional airfoil model has been investigated experimentally in 30 m/s uniform flow (Re = 6.0×10 5). Two exposed electrodes are set on the surface of a NACA0012 airfoil model. For driving SDBD and TED plasma actuators separately, one exposed electrode for applying AC voltages is located at the leading-edge, and DC voltages is applied to another one placed in 41.43 mm downstream from the leading edge. The flow fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreau et al [3] summarized the research conducted in the Plasma European project and introduced fine-wire electrodes, sawtooth electrodes, sliding discharge actuators using three electrodes, and a Multi-DBD PA. Akbıyık et al [4] investigated the effect on the stall angle and lift and drag coefficients for the NACA0015 wing using three types of PAs with different shapes (straight, sawtooth, and square). Asaumi et al [5] conducted a wind tunnel test with a high Reynolds number (Re = 6.0 × 10 5 ) using a tri-electrode PA composed of three electrodes for the NACA0012 blade. They found that the induced velocity of the TED-SD-PA was more than double the induced velocity of the standard PA and reported that the control efficiency could also be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreau et al [3] summarized the research conducted in the Plasma European project and introduced fine-wire electrodes, sawtooth electrodes, sliding discharge actuators using three electrodes, and a Multi-DBD PA. Akbıyık et al [4] investigated the effect on the stall angle and lift and drag coefficients for the NACA0015 wing using three types of PAs with different shapes (straight, sawtooth, and square). Asaumi et al [5] conducted a wind tunnel test with a high Reynolds number (Re = 6.0 × 10 5 ) using a tri-electrode PA composed of three electrodes for the NACA0012 blade. They found that the induced velocity of the TED-SD-PA was more than double the induced velocity of the standard PA and reported that the control efficiency could also be improved.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these advantages, DBD-PAs are expected to be widely utilized in applications intended to enhance the performance of fluid machinery. Several studies have been conducted to this end, the most noteworthy of which include flow-separation control over an airfoil by replacing flaps [5][6][7], slats [7][8][9][10], and synthetic jets [11], and investigations on drag-reduction techniques [12][13][14], cylinder flow control for drag and noise reduction [15][16][17], and flame-stability enhancement [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This adds momentum to the fluid boundary layer over the surface. Previous studies have reported on the effectiveness of this approach in flow-separation control [7][8][9][10] and turbulent drag reduction [12][13][14]. Some researchers have also revealed that the characteristics of the induced flow generated by the DBD-PA vary depending on the applied AC voltage waveform [20][21][22].…”
Section: Introductionmentioning
confidence: 99%